1995
DOI: 10.1007/bf00944606
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1? (IL-1?) production by alveolar macrophages in patients with acute lung diseases: the influence of zinc supplementation

Abstract: The relationship between zinc treatment and interleukin-1 alpha (IL-1 alpha) production by cultured alveolar macrophages (AM) in patients with pulmonary tuberculosis and bacterial pneumonia was investigated. AM (1 x 10(6) cells/ml) from 6 patients with pulmonary tuberculosis, 7 patients with bacterial pneumonia and 4 healthy volunteers were cultured with either two different concentrations of zinc chloride (Znl = 1 microgram/ml and Zn2 = 5 micrograms/ml) or cell culture media alone (control) for an initial per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Zinc supplementation of patients with pulmonary tuberculosis and bacterial pneumonia was shown to increase immune function 32. In a study, it was found that PPD indurations were larger in children receiving zinc and zinc increases the PPD induration size in children irrespective of nutritional status 33…”
Section: Effects Of Tuberculosis On Nutritional Statusmentioning
confidence: 99%
“…Zinc supplementation of patients with pulmonary tuberculosis and bacterial pneumonia was shown to increase immune function 32. In a study, it was found that PPD indurations were larger in children receiving zinc and zinc increases the PPD induration size in children irrespective of nutritional status 33…”
Section: Effects Of Tuberculosis On Nutritional Statusmentioning
confidence: 99%
“…Fan et al (1996) observed that impaired leucocyte adhesion and lymphocyte function in zinc deficient premature infants were reversed following zinc therapy. Abul et al (1995) documented the regulatory role of zinc on the production of IL-1 a from alveolar macrophages of patients with acute lung disease. In addition to these effects, zinc supplements lead to accelerated regeneration of mucosa, increase in the levels of brush border enzymes, enhanced cellular immunity and higher level of secretory antibodies as documented by Folwaczny et al (1997).…”
Section: Zinc and Immune Functionmentioning
confidence: 99%
“…Thus, it was suggested that plasma zinc status is likely a marker for monitoring the severity of disease and the response to therapy (12). In addition, zinc supplementation of patients with pulmonary tuberculosis and bacterial pneumonia was shown to increase immune function (13). Studies in humans and animals have shown that zinc deficiency impairs the synthesis of retinol binding protein (14) and reduces plasma retinol concentrations (15).…”
Section: Introductionmentioning
confidence: 99%